Transforming Legal Values amid Modern and Traditional Social Dynamics A Socio-Legal Perspective - Fiqhan Qaulan Tsaqilan (Fast in Humanities, 2025)
Rapid social changes in modern societies have far-reaching implications for the system of values, including those embedded in the legal order that once grew organically within traditional communities. This study aims to analyze the transformation of legal values within the interaction between modern and traditional societies through a socio-legal perspective. The socio-legal approach is considered relevant because it reveals the reciprocal relationship between law and social reality, explaining how legal norms are shaped and reinterpreted by social, economic, and cultural change. In the context of modernization and globalization, law has shifted from a communal, value-oriented foundation toward a more rational, formal, and individualistic system. Nevertheless, traditional values such as deliberation, mutual cooperation, social justice, and moral balance remain vital for maintaining social cohesion. In Indonesia, the coexistence of customary law, religious law, and state law illustrates the dynamic negotiation of values between the past and the present. This interaction shows that modernity does not eliminate tradition but rather demands continuous adaptation, reinterpretation, and integration of values. Thus, the transformation of legal values is not a process of substitution but a dialectic between continuity and change. The findings of this study are expected to contribute conceptually to the development of socio-legal studies in Indonesia and offer a critical reflection for policymakers in formulating an inclusive, contextual, and socially just legal system that meets the evolving needs of modern society.